2017
DOI: 10.1137/16m1109527
|View full text |Cite
|
Sign up to set email alerts
|

Equilibria for an Aggregation Model with Two Species

Abstract: We consider an aggregation model for two interacting species. The coupling between the species is via their velocities, that incorporate self-and cross-interactions. Our main interest is categorizing the possible steady states of the considered model. Notably, we identify their regions of existence and stability in the parameter space. For assessing the stability we use a combination of variational tools (based on the gradient flow formulation of the model and the associated energy), and linear stability analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…In this paper we study a type of particle system that is less intensively studied: a system with two species, called positive and negative particles [GLP10, CXZ16, DFF13, BBP17, EFK17,vM18]. In our setting, we also consider singular interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we study a type of particle system that is less intensively studied: a system with two species, called positive and negative particles [GLP10, CXZ16, DFF13, BBP17, EFK17,vM18]. In our setting, we also consider singular interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The simplified model for the interacting dislocations which we consider in this paper is a onedimensional interacting particle system with two species (see §1.1). Interacting particle systems with multiple species are of rapidly increasing interest; see, e.g., [CXZ16,DFF13,BBP16,EFK16] and the references therein for applications to dislocation networks, cellular aggregation, granular media, pedestrian movement, opinion formation and predator-pray models. A common challenge in these particle systems is the passage to the many-particle limit.…”
Section: Introductionmentioning
confidence: 99%
“…Discussion and conclusion. Motivated by missing rigorous micro-to-macro connections for dislocation density models, we consider a class of interacting particle system (given by the energy E n (2)) consisting of two species, which is also related to other applications [DFF13, BBP16,EFK16]. For the physically interesting scaling regimes of the parameters α n and γ n , we prove that E n Γ-converges to E (Theorem 1.1).…”
mentioning
confidence: 99%
“…with generic cross-interaction kernels K ρ and K η is investigated in [22], whereas studies on the shape of stationary states can be found in [17,27]. Concerning the predator-prey modelling and patterns formation, in [15,46] a minimal version of (1) has been considered with only one predator and arbitrarily many prey subject to (different) singular potentials.…”
Section: 3mentioning
confidence: 99%
“…The goal of this paper is to show that the model above catches one of the main features that occur in nature, namely the formation of spatial patterns where the predators are surrounded of empty zones and the prey aggregates around, that is usually observed in fish schools or in flock of sheeps, see [32,38]. In the fully aggregative case, namely system (2) with d 1 = d 2 = 0, the formation of these types of patterns has been studied in several papers, see [15,27,21,46] and references therein.…”
mentioning
confidence: 98%